2023
DOI: 10.1039/d2fo01832b
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between sleep quality and dietary inflammation on frailty: NHANES 2005–2008

Abstract: Aims: The underlying mechanism of both sleep disorder and frailty was chronic inflammation, which could be reflected by Dietary inflammatory index (DII). Therefore, we aimed to explore the association...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…The different prevalence observed across these studies can be mainly explained by the differences in study populations, sample sizes and instruments used to assess sleep quality. Given the moderate-to-high prevalence of poor sleep quality found in this study and the link between poor sleep quality and subsequent adverse health outcomes among patients with T2DM found in previous studies,31–33 it is highly recommended for the primary healthcare workers to screen patients with T2DM for sleep quality on a regular basis in Hunan, China, and take effective interventions such as cognitive behavioural therapy, muscle endurance training combined with walking and dietary supplements to improve sleep quality 34–36…”
Section: Discussionmentioning
confidence: 87%
“…The different prevalence observed across these studies can be mainly explained by the differences in study populations, sample sizes and instruments used to assess sleep quality. Given the moderate-to-high prevalence of poor sleep quality found in this study and the link between poor sleep quality and subsequent adverse health outcomes among patients with T2DM found in previous studies,31–33 it is highly recommended for the primary healthcare workers to screen patients with T2DM for sleep quality on a regular basis in Hunan, China, and take effective interventions such as cognitive behavioural therapy, muscle endurance training combined with walking and dietary supplements to improve sleep quality 34–36…”
Section: Discussionmentioning
confidence: 87%
“…IL-1β has been linked to increased growth hormone-releasing hormone and improved non-rapid-eye-movement sleep in humans ( 55 ). The NHANES study found inflammation as a potential relationship between sleep problems and frailty, and anti-inflammatory diets can reduce the negative effects of poor sleep quality on frailty ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Participants were divided into 2 subgroups: FI ≤ 0.2 was considered fit and FI > 0.2 was considered frail. 13…”
Section: Frailty Index (Fi)mentioning
confidence: 99%
“…9 Since the introduction of the free radical theory of aging, oxidative stress has been identified as one of the major causes of frailty in several previous studies. [10][11][12] As the effects of a wide range of dietary nutrients [13][14][15] and lifestyle-related behaviors 16 on oxidative stress pathways have been discovered, there has been increasing interest in the possible role of these factors in frailty. There are studies showing that the early stages of frailty can be improved through adequate nutritional intake and physical activity regimes.…”
Section: Introductionmentioning
confidence: 99%